Eco-biofabrication of silver nanoparticles from Azadirachta indica, Gymnema sylvestre, and Moringa oleifera for lung cancer treatment - Tanya Muthu; Ravi Adusumalli; Sathish Kumar Vemuri; M. Indira Devi; P. Pavan Kumar; Rajkiran Reddy Banala; A. V. Gurava Reddy (Journal of the Egyptian National Cancer Institute)
Abstract Introduction Silver nanoparticles (AgNPs) derived from natural sources have garnered significant attention due to their unique properties and eco-friendly production methods. With lung cancer remaining a major global health issue, there is a continuous need for novel and effective therapeutic approaches beyond conventional treatments such as chemotherapy, immunotherapy, and targeted therapies. Objective This study aims to synthesize AgNPs using plant extracts from Gymnema sylvestre, Moringa oleifera, and Azadirachta indica and to evaluate their anticancer activity, particularly their effects on gene expression in A549 lung cancer cells. Methods AgNPs were synthesized using green chemistry techniques and characterized by X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). Gene expression studies were performed to assess the impact of AgNPs on cancer-related genes such as VEGF and CYCLIN-D1. Cytotoxicity assays were conducted on A549 cells to determine the anticancer potential of the synthesized AgNPs compared to plant extracts alone. Results XRD confirmed the formation of crystalline AgNPs, while FTIR indicated the presence of bioactive compounds interacting with the nanoparticles. Gene expression analysis revealed significant downregulation of VEGF and CYCLIN-D1, suggesting inhibitory effects on angiogenesis and cell cycle progression. The synthesized AgNPs exhibited potent cytotoxic activity against A549 cells, with enhanced efficacy compared to the leaf extracts alone. Conclusion The study highlights the potential of AgNPs synthesized from medicinal plant extracts as promising candidates for lung cancer therapy. Their environmentally sustainable production, combined with their ability to target key cancer pathways, positions them as innovative and affordable therapeutic agents in the field of nanomedicine.